2019
DOI: 10.1007/s00125-019-05062-x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory, randomised, placebo-controlled, 14 day trial of the soluble guanylate cyclase stimulator praliciguat in participants with type 2 diabetes and hypertension

Abstract: Aims/hypothesis Praliciguat (IW-1973), a soluble guanylate cyclase stimulator, amplifies nitric oxide signalling. This exploratory trial investigated the safety, tolerability, pharmacokinetic profile and pharmacodynamic effects of praliciguat in individuals with type 2 diabetes and hypertension. Methods This Phase IIA, double-blind, placebo-controlled trial investigated praliciguat in 26 participants with type 2 diabetes and hypertension on stable glucose-and BP-lowering therapies. Participants were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
6
21
0
1
Order By: Relevance
“…In this study, praliciguat treatment was also associated with modest reductions in certain metabolic measures, including HbA1c and total and LDL cholesterol levels. This is consistent with clinical data on praliciguat in people with type 2 diabetes and hypertension (36), as well as findings from nonclinical studies (36,45,46). Possible mechanisms of Intent-to-treat population.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, praliciguat treatment was also associated with modest reductions in certain metabolic measures, including HbA1c and total and LDL cholesterol levels. This is consistent with clinical data on praliciguat in people with type 2 diabetes and hypertension (36), as well as findings from nonclinical studies (36,45,46). Possible mechanisms of Intent-to-treat population.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous clinical studies (36,37), praliciguat treatment was associated with modest decreases in systemic BP and changes in heart rate, presumably compensatory. These hemodynamic effects are consistent with the known pharmacology of sGC stimulators (23).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although the mechanism is not completely understood, our data add to a growing body of evidence that pharmacological stimulation of sGC may have favorable effects on metabolism in obesity and metabolic syndrome. In 2015, it was reported that the sGC stimulator BAY 41-8543 protected against weight gain and improved the diabetic phenotype in a diet-induced obesity mouse model (Hoffmann et al, 2015), and in a study in 26 patients with diabetes and hypertension, 14 days of treatment with the sGC stimulator praliciguat reduced fasting glucose level and total and LDL cholesterol levels (Hanrahan et al, 2020).…”
Section: Olinciguat Treatment Affected Cardiometabolic Risk Factors Amentioning
confidence: 99%